A method of local skin perfusion detection - Hálek, J (Journal of medical systems, 2000)
On the epidermal surface there are inhomogeneities which manifest as, among other things, lower local impedance. These regions include Head's zones, sweat glands, and also the so-called acupuncture points. The aim of this paper is to examine the effect of skin perfusion on epidermal impedance at the acupuncture points. When measuring epidermis impedance in the local (acupuncture) points the method of impedance plethysmography was applied. Both the method of four electrode measurement at the constant current and the method of two electrode measurement by means of the different and indifferent electrode as well were engaged. First, we had to uncover the size of the action skin points which was made by means of a different micro-electrode developed by us. The effect of some factors on the reproducibility and comparability of the values measured was evaluated. The attention was focused mainly on the questions of the pressure of the different electrode on the skin surface, magnitude and waveform of the exciting current, and so on. The authors demonstrate the impossibility to measure changes in skin impedance in the acupuncture points, in dependence on the blood perfusion--which was due to the high serial resistance between the point measured in the acupuncture place when the four-electrode measurement was applied, on the other side.
Keywords: elektrody; fyziologie kůže; akupunkturní body; Skin Physiological Phenomena; Acupuncture Points; Surface Properties; lidé; povrchové vlastnosti; elektrofyziologie; Humans; kůže; elektrická impedance; Electrophysiology; Electrodes; Skin; Electric Impedance